What Drives Giving in Extensive Welfare States? The Case of Germany - Sarah Borgloh (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Considerable empirical research exists on donations in the US and their determinants, including estimations of the income and price elasticity of giving. By contrast, less is known about the determinants of countries with an extensive welfare state. We address this deficiency by studying the drivers of charitable giving in Germany, a country with a highly developed welfare state, using tax return data of the years 2001 to 2003. Our study not only expands the literature by adding another country. Moreover, it uses modern econometric methods which account for the selection process inherent in charitable contributions. Our results suggest no significant differences between donors in the US and Germany with respect to income and price elasticities indicating that the mechanisms underlying the act of giving are similar for countries with highly different welfare state traditions.
Keywords: H24; H41; 330; private donations; income elasticity; price elasticity; welfare state; Spende; Wohltätigkeit; Sozialstaat; Steuerbegünstigung; Preiselastizität; Einkommenselastizität; Deutschland